2015
DOI: 10.1007/s00203-015-1116-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of Listeria monocytogenes ATCC 19115 in response to simultaneous triple stresses

Abstract: Listeria monocytogenes can cause listeriosis in humans through consumption of contaminated food. L. monocytogenes can adapt and grow in a vast array of physiochemical stresses in the food production environment. In this study, we performed a proteomics strategy in order to investigate how L. monocytogenes survives with a simultaneous exposure to low pH, high salinity and low temperature. The results showed that the adaptation processes mainly affected the biochemical pathways related to protein synthesis, oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…As for many other bacterial pathogens, L. monocytogenes activates the expression of virulence genes at host body temperature (23). Throughout the years, multiple studies have been published exploring Listeria 's temperature adaptation, either through physicochemical tests (21, 2429), genomic and transcriptomic methods (3038), and also through metabolic and proteomic approaches (3944). However, there is still a knowledge gap in the comparison of subproteomic changes to different temperatures, particularly in the biofilm mode of growth.…”
Section: Introductionmentioning
confidence: 99%
“…As for many other bacterial pathogens, L. monocytogenes activates the expression of virulence genes at host body temperature (23). Throughout the years, multiple studies have been published exploring Listeria 's temperature adaptation, either through physicochemical tests (21, 2429), genomic and transcriptomic methods (3038), and also through metabolic and proteomic approaches (3944). However, there is still a knowledge gap in the comparison of subproteomic changes to different temperatures, particularly in the biofilm mode of growth.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have carried out proteomics analyses of L. monocytogenes exposed to single-or dual-stress (acid and salt) conditions [5,7,14,[29][30][31][32][33][34][35][36]. However, the response of the proteome of L. monocytogenes to simultaneous exposure to acid and salt for a time-course study had not been investigated and was therefore examined in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, adaptation to different antimicrobials leads to modification of the amount of some ribosomal proteins involved in translation, ribosomal structure and biogenesis (30S ribosomal proteins S1, S2, S3, and S8 and 50S ribosomal proteins L5, L7/L12, L25, and L31). Previously, L. monocytogenes cells were shown to decrease the level of S1 protein under combined stresses (low pH, high salinity and low temperature) (He et al, 2015). Guevara et al (2015) showed that the level of L7/L12 increased during moderate heat, carvacrol and thymol treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent progress in elucidating the details of the L. monocytogenes genome, the mechanisms this bacterium adapts to natural antimicrobial compounds remains largely unclear (NicAogáin and O’Byrne, 2016; Braschi et al, 2018a,b). Studies on the adaptation of L. monocytogenes to natural antimicrobial compounds are crucial to highlight the relationship between stress and virulence and to optimize the protocols used for food production (Chaturongakul et al, 2008; Bowman et al, 2010; He et al, 2015).…”
Section: Introductionmentioning
confidence: 99%